HUBUNGAN KECEPATAN LARI 60 METER DENGAN HASIL LOMPAT JAUH PADA SISWA PUTERA KELAS XI JURUSAN ILMU PENGETAHUAN SOSIAL SMAN 1 SEDINGINAN KECAMATAN TANAH PUTIH - Irma Suryani; Ramadi '; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the low long jump results being owned by the male student of class XI majoring in social science. KKM determined from only a couple of students who achieve it. The problem is evident from observations of researchers at the time learnin procces at the school, it is suspected because of the running speeed owned by the students. Therefore, the purpose of this study was to determine whether there is a corelation with a running speed of 60 meter with long jump results male students of class XI majoring in social science. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is a running speed of 60 meters, while the dependent variable (Y) is the long jump. This research data obtained from the test run 60 meters and long jump test. The sample in this study is the mael students of class XI majoring in social science a total of 11 people (purposive sampling). Based on the research results can be concluded as follows: corelation variable X with variable Y obtained rhitung = 0,63> rtabel = 0.602, then there is a corelation between variables X with variables tested Y. Where significance include the distribution of t, means thitung> ttabel ( 2.43> 1.83) therefore Ho rejected and Ha accepted. Conclusion The hypothesis is accepted at significance level α = 0:05 in other words there is a significant correlation between the speed to run 60 meters and long jump results male students in class XI Majoring IPS SMAN 1 Sedinginan Tanah Putih District.Keywords : Speed Runngin 60 M, Long Jump